Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To solve for [tex]\(a^2\)[/tex] in the given isosceles triangle [tex]\(ABC\)[/tex] where angle [tex]\(A = \frac{\pi}{6}\)[/tex] and sides [tex]\(b = c = 5\)[/tex], we can utilize the Law of Cosines.
The Law of Cosines states that for any triangle with sides [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex], and an angle [tex]\(A\)[/tex] opposite to side [tex]\(a\)[/tex], the following relationship holds:
[tex]\[ a^2 = b^2 + c^2 - 2bc \cos(A) \][/tex]
Given:
[tex]\[ A = \frac{\pi}{6}, \quad b = 5, \quad c = 5 \][/tex]
First, let's calculate [tex]\(\cos\left(\frac{\pi}{6}\right)\)[/tex]. We know that:
[tex]\[ \cos\left(\frac{\pi}{6}\right) = \frac{\sqrt{3}}{2} \][/tex]
Now, substituting the values into the Law of Cosines formula:
[tex]\[ a^2 = 5^2 + 5^2 - 2 \cdot 5 \cdot 5 \cdot \cos\left(\frac{\pi}{6}\right) \][/tex]
Substitute [tex]\(\cos\left(\frac{\pi}{6}\right)\)[/tex]:
[tex]\[ a^2 = 25 + 25 - 2 \cdot 5 \cdot 5 \cdot \frac{\sqrt{3}}{2} \][/tex]
Simplify the expression step-by-step:
[tex]\[ a^2 = 25 + 25 - 25\sqrt{3} \][/tex]
[tex]\[ a^2 = 50 - 25\sqrt{3} \][/tex]
Therefore, the length of [tex]\(a^2\)[/tex] is:
[tex]\[ a^2 = 25(2 - \sqrt{3}) \][/tex]
Comparing this result with the given choices, we find:
A. [tex]\(5^2(2-\sqrt{3})\)[/tex]
Thus, the correct answer is [tex]\(A\)[/tex].
The Law of Cosines states that for any triangle with sides [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex], and an angle [tex]\(A\)[/tex] opposite to side [tex]\(a\)[/tex], the following relationship holds:
[tex]\[ a^2 = b^2 + c^2 - 2bc \cos(A) \][/tex]
Given:
[tex]\[ A = \frac{\pi}{6}, \quad b = 5, \quad c = 5 \][/tex]
First, let's calculate [tex]\(\cos\left(\frac{\pi}{6}\right)\)[/tex]. We know that:
[tex]\[ \cos\left(\frac{\pi}{6}\right) = \frac{\sqrt{3}}{2} \][/tex]
Now, substituting the values into the Law of Cosines formula:
[tex]\[ a^2 = 5^2 + 5^2 - 2 \cdot 5 \cdot 5 \cdot \cos\left(\frac{\pi}{6}\right) \][/tex]
Substitute [tex]\(\cos\left(\frac{\pi}{6}\right)\)[/tex]:
[tex]\[ a^2 = 25 + 25 - 2 \cdot 5 \cdot 5 \cdot \frac{\sqrt{3}}{2} \][/tex]
Simplify the expression step-by-step:
[tex]\[ a^2 = 25 + 25 - 25\sqrt{3} \][/tex]
[tex]\[ a^2 = 50 - 25\sqrt{3} \][/tex]
Therefore, the length of [tex]\(a^2\)[/tex] is:
[tex]\[ a^2 = 25(2 - \sqrt{3}) \][/tex]
Comparing this result with the given choices, we find:
A. [tex]\(5^2(2-\sqrt{3})\)[/tex]
Thus, the correct answer is [tex]\(A\)[/tex].
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.